Polymorphisms in B cell co-stimulatory genes are associated with IgG antibody responses against blood-stage proteins of plasmodium vivax - Cassiano, Gustavo C. [UNESP]; Furini, Adriana A. C.; Capobianco, Marcela P. [UNESP]; Storti-Melo, Luciane M.; Cunha, Maristela G.; Kano, Flora S.; Carvalho, Luzia H.; Soares, Irene S.; Santos, Sidney E.; Póvoa, Marinete M.; Machado, Ricardo L. D. [UNESP] (My University, 2016)
The development of an effective immune response can help decrease mortality from malaria and its clinical symptoms. However, this mechanism is complex and has significant inter-individual variation, most likely owing to the genetic contribution of the human host. Therefore, this study aimed to investigate the influence of polymorphisms in genes involved in the costimulation of B-lymphocytes in the naturally acquired humoral immune response against proteins of the asexual stage of Plasmodium vivax. A total of 319 individuals living in an area of malaria transmission in the Brazilian Amazon were genotyped for four SNPs in the genes CD40, CD40L, BLYS and CD86. In addition, IgG antibodies against P. vivax apical membrane antigen 1 (PvAMA-1), Duffy binding protein (PvDBP) and merozoite surface protein 1 (PvMSP-119) were detected by ELISA. The SNP BLYS -871C>T was associated with the frequency of IgG responders to PvAMA-1 and PvMSP-119. The SNP CD40-1C>T was associated with the IgG response against PvDBP, whereas IgG antibody titers against PvMSP-119 were influenced by the polymorphism CD86 + 1057G>A. These data may help to elucidate the immunological aspects of vivax malaria and consequently assist in the design of malaria vaccines.